The axiological approach to the training of students of pedagogical universities - Smyrnova, Tetiana A.; Bilova, Nataliia K.; Lynenko, Alla F.; Osadchaya, Tatyana V.; Levytska, Irina M. (Linguistics and Culture Review, 2021)
The axiological approach to the education impacts future professional musician’s values and ability to solve professional problems and challenges. This research is aimed at studying the principles of the axiological approach and its possible application in the pedagogical process. Theoretical and practical research on the use of axiological approach in the theory and practice of music pedagogical education was conducted. Pedagogical methods such as questionnaire, observation, testing, group and individual interviews were used. The definition of the axiological approach was given. Effective means of its developing were presented. It was found that integration of axiological, systemic, culturological approaches allows to deepen and diversify the structural and semantic characteristics of the axiology sphere of higher institutions of music and music-pedagogical education. The prospects for further research were found including the necessity to identify the specifics of the development of axiological competence in students of higher art educational institutions.